Why health professions education needs functional linguistics: the power of 'stealth words'. Issue 12 (28th August 2019) - Konopasky, Abigail; Ramani, Divya; Ohmer, Megan; Durning, Steven J; Artino, Anthony R; Battista, Alexis
Abstract : Context: Language is one of the primary modalities for teaching and learning in the health professions in contexts ranging from the more formal teaching relationships of medical school to the guided practice of trainees through continuing education and the deliberate practice of lifelong learning. Yet linguistic analysis, with the possible exception of discourse analysis, has not become a core methodological tool in the field of health professions education (HPE). The purpose of this paper is to argue for the more widespread adoption of one particular approach to linguistics, one that examines less of what learners and instructors say and looks more at how they say it: functional linguistics. Functional linguistics: the power of 'stealth words': This approach theorises and structures the functions of language, regularly focusing attention on 'stealth words' such as I, but and was . Drawing on a rich body of literature in linguistics, psychology, the learning sciences and some early work in HPE, we demonstrate how functional linguistic tools can be applied to better understand learners' and instructors' beliefs, reasoning processes, values and emotions. Functional linguistics and reflection: an application of stealth words: A brief qualitative analysis of one tool – analysis of the generic use of 'you' to mean 'one' or 'anyone' – demonstrates how functional linguistics can offer insight into physicians' bids for credibility and alignment as they think aloud about their clinical reasoning. Functional linguistics and hpe: future directions: Finally, we offer suggestions for how functional linguistic tools might address questions and gaps in four active research areas in HPE: reflection; emotion and reasoning; learning in simulated contexts, and self‐regulated learning. Conclusions: We argue that the words used by learners, instructors and practitioners in the health professions as they move through undergraduate and graduate training into practice can offer clues that will help researchers, instructors and colleagues to better support them. Abstract : Although words like we, you, the, and but are easy to overlook, functional linguistics offers insight into how these 'stealth words' can inform us about learners' and instructors' beliefs, reasoning processes, values, and emotions.